Analisis Pengaruh Firm Size dan Sales Growth Terhadap Return Saham - Anisa Maramis; Nor Norisanti; Kokom Komariah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the effect of Firm Size and Sales Growth on Stock Return in food and beverage sub-sector companies in 2017-2020. The method used is a quantitative method through an associative descriptive approach. The sample used in this study is by using purposive sampling. Of the 30 members of the food and beverage sub-sector companies, 10 companies were selected as samples. Using secondary data collection techniques and multiple linear regression analysis methods to test this research. The results of this study indicate that there is no influence between firm size on stock returns and there is an influence between sales growth on stock returns in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. Keywords : Firm Size, Sales Growth, Stock Return